TDP-43 Mutation Affects Stress Granule Dynamics in Differentiated NSC-34 Motoneuron-Like Cells - Ding, Qiao; Chaplin, Justin; Morris, Matthew J.; Hilliard, Massimo A.; Wolvetang, Ernst; Ng, Dominic C. H.; Noakes, Peter G. (Frontiers in Cell and Developmental Biology, 2021)
Amyotrophic Lateral Sclerosis (ALS) is characterized by degeneration of motor neurons in the brain and spinal cord. Cytoplasmic inclusions of TDP-43 are frequently reported in motor neurons of ALS patients. TDP-43 has also been shown to associate with stress granules (SGs), a complex of proteins and mRNAs formed in response to stress stimuli that temporarily sequester mRNA translation. The effect of pathogenic TDP-43 mutations within glycine-rich regions (where the majority of ALS-causing TDP-43 mutations occur) on SG dynamics in motor neurons is poorly understood. To address this issue, we generated murine NSC-34 cell lines that stably over-express wild type TDP-43 (TDP-43WT) or mutant forms (ALS-causing TDP-43 mutations TDP-43A315T or TDP-43M337V). We next differentiated these NSC-34 lines into motoneuron-like cells and evaluated SG formation and disassembly kinetics in response to oxidative or osmotic stress treatment. Wild type and mutant TDP-43 were retained in the nucleus following exposure to arsenite-induced oxidative stress. Upon arsenite removal, mutant TDP-43 accumulated within HuR positive SGs in the cytoplasm, whereas TDP-43WT remained in the nucleus. 24 hrs following arsenite removal, all SGs were disassembled in both wild type and mutant TDP-43 expressing cells. By contrast, we observed significant differences in the dynamics of mutant TDP-43 association with SGs in response to hyperosmotic stress. Specifically, in response to sorbitol treatment, TDP-43WT remained in the nucleus, whereas mutant TDP-43 relocalized to HuR positive SGs in the cytoplasm, resulting in a significant increase in TDP-43 SGs numbers. These SGs remained assembled for 24 hrs following removal of sorbitol. Our data reveal that under stress conditions the rates of SG formation and disassembly is modulated by TDP-43 mutations associated with ALS, and suggest that this may be an early event in the seeding of insoluble cytoplasmic inclusions observed in ALS.